2001
DOI: 10.1143/jjap.40.3277
|View full text |Cite
|
Sign up to set email alerts
|

Study on Helical Structure of the B4 Phase Formed from Achiral Banana-Shaped Molecule

Abstract: The helical structure of the B4 phase in the banana-shaped molecules, the 1,3-benzene bis[4-(4-n-alkoxyphenyliminomethyl) benzoate] (P-n-O-PIMB) series, has been studied by means of optical microscopy, X-ray diffraction and circular dichroism for homogeneously and homeotropically aligned cells. The homogeneously aligned cells showed a transparent blue color and a circular dichroism at about 400 nm, indicating the existence of a helical structure. Detailed texture observation also reveals the existence of two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
137
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 38 publications
9
137
0
Order By: Relevance
“…[4] The first observation of macroscopic chiral domains, however, was in the B4 phase of P-9-OPIMB homologs, [5] where large left-and right-handed chiral domains were distinguished under decrossed polarizer and analyzer. These domains immediately suggested some kind of helical structure [6] and it has since been confirmed that left-and right-handed helical nanofilaments are the structural basis of the B4 phase. [7,8] The bentcore molecules form well-defined smectic layers with in-plane hexatic order, the coupling of macroscopic polarization and tilt of the molecular planes making the layers chiral (Figure 1 a).…”
Section: Introductionmentioning
confidence: 86%
“…[4] The first observation of macroscopic chiral domains, however, was in the B4 phase of P-9-OPIMB homologs, [5] where large left-and right-handed chiral domains were distinguished under decrossed polarizer and analyzer. These domains immediately suggested some kind of helical structure [6] and it has since been confirmed that left-and right-handed helical nanofilaments are the structural basis of the B4 phase. [7,8] The bentcore molecules form well-defined smectic layers with in-plane hexatic order, the coupling of macroscopic polarization and tilt of the molecular planes making the layers chiral (Figure 1 a).…”
Section: Introductionmentioning
confidence: 86%
“…[41][42][43][44][45] The polarity and chirality as well as frustration have become a world wide topics in the liquid crystalline field. 46 It should be emphasized that studies on these exotic phases start from the studies on the polymeric effects in main-chain LC polymers.…”
Section: Layer Structure Responsible For Distinct X-ray Pattern Showimentioning
confidence: 99%
“…shaped molecules can be observed in their unique mesophases such as B 2 phase with electro-optical switchable property (the smectic layered chirality induced by the existence of the polar direction and the tilting molecular director with respect to the layer normal) [36][37][38][39][40] , B 4 phase with opposite optical activity (the different chiral domains formed from the helical morphology which is similar to the twist grain boundary phase), [41][42][43][44] and B 7 phase with macroscopic spiral and more complicated textures. [45][46][47][48][49] Watanabe and co-workers suggested that the asymmetric twisting conformation which is resulted from the ester linkage groups connecting the central phenyl ring with the side wings seems to be one of the origins for the formation of the helical morphology.…”
Section: Introductionmentioning
confidence: 99%